Correction to: Spil mediated sEH overexpression contributes to the senescence of alveolar epithelial cells during pulmonary fibrosis in mice - Chen-Yu Zhang; Wen-Jing Zhong; Jin-Tong Yang; Yan-Ling Qiu; Han-Xi Sha; An-Jun Ou; Yu-Biao Liu; Xiao-Ting Huang; Yong Zhou; Jia-Xi Duan; Cha-Xiang Guan (Journal of Molecular Medicine, 2026)

Spil-mediated sEH overexpression contributes to the senescence of alveolar epithelial cells during pulmonary fibrosis in mice - Chen-Yu Zhang; Wen-Jing Zhong; Jin-Tong Yang; Yan-Ling Qiu; Han-Xi Sha; An-Jun Ou; Yu-Biao Liu; Xiao-Ting Huang; Yong Zhou; Jia-Xi Duan; Cha-Xiang Guan (Journal of Molecular Medicine, 2026)

Heterocyclic aromatic nitrogen carbon dots as sprayable fluorescent probes for the identification of real chemical warfare agents - Hanseung Kim; Hyeonho Jeong; Byeongjun Jeon; Myeong Seo Cha; Donghyeon Kim; Yanamala Poojitha; Soobin Han; Yonghyeon Park; Jungjoo Lee; Moein Safarkhani; Fahimeh Taghavimandi; Young-Su Jeong; et al. (Chemical Engineering Journal, 2026)

Polysaccharide-based hydrogel strain sensors: Materials design, sensing mechanisms, applications, and challenges - Dinesh K. Patel; Junmin Cha; Sung Soo Han (Carbohydrate Polymers, 2026)

Morph-specific strength of directional selection on number of flowers in Primula alpicola - Yun Wu; Hu-Han Yi; Yong-Peng Cha; Jin-Song Chen (Plant Ecology, 2026)

Trade-offs between photosynthetic capacity and structural economy underlie the rapid proliferation of floating Ulva prolifera - Ruili Niu; Cancan Xia; Min Cha; Cui Han; Bojian Zhong; Xiaojie Liu (Harmful Algae, 2026)

Molecular marker-based source apportionment of PM2.5-Associated organic compounds in a transboundary-influenced urbanized receptor region - Ji-Won Jeon; Hyo-Won Lee; Young-Ji Han; Seung-Ha Lee; Seung-Hwan Cha; Jung-Min Park (Environmental Research, 2026)

Seasonality and aerosol microenvironment-associated processing of organic aerosol in a humid inland city - Hyo-Won Lee; Ji-Won Jeon; Young-Ji Han; Seung-Ha Lee; Hyun-Gu Jung; Seung-Hwan Cha; Ha-Yoon Jeong; Jung-Min Park; Jefferey L. Collett Jr. (Journal of Hazardous Materials, 2026)

Corrigendum to “Starch nanoparticle platform for oral delivery of sinigrin in colitis therapy” [Carbohydrate Polymers 367 (2025) 124032] - Hazzel Joy Adra; Hanvit Cha; Moon Han Chang; Dong-Gook Kang; Su-min Kwon; Sang-Mook You; Yu Ri Jeong; Chae Hwan Lee; Ki Sung Park; Seung Pil Pack; Jin Hyup Lee; Young-Rok Kim (Carbohydrate Polymers, 2026)

A Novel Strain Bifidobacterium longum subsp. longum HN001 Ameliorates High-Fat Diet-Induced Obesity in Mice Through Microbiome-Associated Short-Chain Fatty Acids - Chae Hwan Lee; Youngji Han; Joo Young Ryu; Minseo Jung; Chae Rin Park; Mi Ran Jang; Youn Gil Kwak; Hanvit Cha; Jin Hyup Lee (Probiotics and Antimicrobial Proteins, 2026)

Mediating role of the maternal placental growth factor levels on association between ozone exposure and adverse pregnancy outcomes - Yajuan Wang; Yuanyuan Yu; Yang Li; Xiaoli Gao; Wenjun Fan; Xuening Bai; Xiaozhou Li; Jiayan Zhou; Ying Zhang; Qisijing Liu; Chen Li; Rongrong Wu; et al. (Environmental Research, 2026)

Caseazins R−Y, cytotoxic podocarpane diterpenoids from Casearia kurzii - Xue-Wen Wu; Qiong Wei; Xia Pu; Chun-Mei Cha; Rui Li; Yin-Qiao Huang; Rui-Han Zhang; Xiao-Li Li; Hong-Liang Li; Wei-Lie Xiao (Phytochemistry, 2026)

β–phase polymer-driven enhanced powder flowability and microstructure uniformity for stable and fast dry-processed electrode - Min Jang; Hyeongseok Shim; Sijeong Park; Hyeju Shin; Jeong-Rae Jo; Wooyoung Jin; Hyungyeon Cha; Jung Hoon Kim; Joong Tark Han; Gyujin Song; Sinho Choi (Chemical Engineering Journal, 2025)

Biochar utilization in thermochemical biodiesel production from perilla seed - Taewoo Lee; Gyeongnam Park; Hoyeon Cha; Hyungseok Nam; Han-Woo Kim; Eilhann E. Kwon (Chemical Engineering Journal, 2025)

Optimal chemokine receptors for enhancing immune cell trafficking in adoptive cell therapy - DoYeon Han; Byung-Kwan Jeong; Jong Moo Hong; Jeong-Han Seo; GunHee Lee; Kwanghee Kim; Chorong Hong; Hyeonjin Lee; Su Min Cha; Jong Hyeok Kim; Taehyun Park; Gyungyub Gong; et al. (Immunologic Research, 2025)

Blocking triggering receptors expressed on myeloid cell-1 alleviates alveolar epithelial cell senescence by inhibiting oxidative stress in pulmonary fibrosis - Wen-Jing Zhong; Jian-Bing Xiong; Chen-Yu Zhang; Ling Jin; Nan-Shi-Yu Yang; Han-Xi Sha; Yu-Biao Liu; Jia-Xi Duan; Cha-Xiang Guan; Yong Zhou; Feng Su (Histochemistry and Cell Biology, 2025)

Influence of the drying method on the physicochemical properties, volatile compounds, and odor characteristics of edible insect oils - Ji Yoon Cha; Mi-Ran Kim; Yea-Ji Kim; Jeong Heon Kim; Jaejoon Han; Yun-Sang Choi (Food Research International, 2025)

Using natural nitrites from Angelica keiskei and high hydrostatic pressure treatment for producing high-quality cured pork loin with significant nitrous pigment formation - Yea-Ji Kim; Jeong-Heon Kim; Ji Yoon Cha; Tae-Kyung Kim; Jong Hyeon Han; Sung Gu Han; Yun-Sang Choi (Food Chemistry, 2025)

Electrolyte and reaction heat behavior in blended aqueous solutions of poly and mono alkanolamine for carbon capture processes: CO2–AEEA–DIPA–H2O system - Shaukat Ali Mazari; Min-Kyeong Oh; Jin-Young Cha; Seong-Yun Bae; Sijan Devkota; Min-Seo Yun; Ankit Belbase; Eun-Uk Yu; Sang-Jun Han; Kyung-Min Kim; Kyungjae Tak; Ung Lee; et al. (Chemical Engineering Journal, 2025)

2D intercalated charge confinement and surface modification in a montmorillonite-based composite for an anti-bacterial and biodegradable self-powered sensor - Seunghye Han; Jungchul Park; Seong Wook Lee; Jiwoo Lee; Seohyun Lee; Hyemin Bak; Seokjun Cha; Jihyun Bae; Jeong Ho Chang; Jong-Jin Park (Chemical Engineering Journal, 2025)

Starch nanoparticle platform for oral delivery of sinigrin in colitis therapy - Hazzel Joy Adra; Hanvit Cha; Moon Han Chang; Dong-Gook Kang; Su-min Kwon; Sang-Mook You; Yu Ri Jeong; Chae Hwan Lee; Ki Sung Park; Seung Pil Pack; Jin Hyup Lee; Young-Rok Kim (Carbohydrate Polymers, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Establishment of Immune-Evasive iPSCs from PBMCs Using B2M Knockout and CD47/HLA-E Overexpression - Cha Yeon Kim; Cholong Jeong; Yeon-Ju Jeong; Young Hoon Sung; Youngjin Han; Changmo Hwang (Tissue Engineering and Regenerative Medicine, 2025)

Modeling ecosystem-wide responses to environmental stressors: A multi-trophic hierarchical Bayesian network approach - Taeseung Park; Jaegwan Park; Dogeon Lee; Jounggyu Jung; Geumbit Hwang; Jeongsuk Moon; Hyun-Han Kwon; YoonKyung Cha (Journal of Environmental Management, 2025)

Distributions and compositional characteristics of per- and polyfluoroalkyl substances (PFASs) in sediments of the regional seas of South Korea - Sunmi Yang; Jiyun Gwak; Jihyun Cha; Kiho Park; Youngnam Kim; Sea-Yong Kim; Yeonjung Lee; Dong Han Choi; Kongtae Ra; Hyo-Bang Moon; Seongjin Hong (Marine Pollution Bulletin, 2025)

Sequential slot-die coating of perovskite solar cell modules under ambient conditions with precise phase-transition control - Chia-Feng Li; Shih-Han Huang; You-Ren Chen; Hou-Chin Cha; Ssu-Yung Chung; Yu-Hung Hsiao; Feng-Yu Tsai; Yu-Ching Huang (Chemical Engineering Journal, 2025)

Angiopoietin-1 and Tie2-Based Dual Cell Therapy Enhances Antiangiogenic Barrier Function in a Retina-Mimetic Model for Neovascular Retinal Disease - Cha Yeon Kim; Cholong Jeong; Youngjin Han; Changmo Hwang (Tissue Engineering and Regenerative Medicine, 2025)

Comparison of antioxidant properties of dried and fresh daylily flowers and their impact on lipid and protein oxidation during cooking and in vitro digestion of mutton - Yucan Wu; Lihan Cha; Dong Han; Qiang Xie; Xiaobing Liu; Chunhui Zhang; Jing Wang; Feng Huang (International Journal of Gastronomy and Food Science, 2025)

Spatiotemporal dynamics of summer chlorophyll-a concentrations under varying drought conditions in a hierarchical Bayesian model - Pamela Sofia Fabian; YoonKyung Cha; Kyung-A You; Hyun-Han Kwon (Chemical Engineering Journal, 2025)

Metagenomic insights into the carbon decomposition of plant and microbial biomass in forests across biomes - Xinyu Cha; Shuohong Zhang; Meixuan Wang; Zhenghu Zhou; Jian Deng; Gang He; Fazhu Zhao; Gaihe Yang; Xinhui Han; Chengjie Ren (Soil Ecology Letters, 2025)

Leveraging large language models in pharmacometrics: evaluation of NONMEM output interpretation and simulation capabilities - Hwa Jun Cha; Kyuyeon Choe; Euibeom Shin; Murali Ramanathan; Sungpil Han (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Backtracking identification techniques for predicting unclear bacterial taxonomy at species level: molecular diagnosis-based bacterial classification - Yeseul Choi; Jinuk Jeong; Minseo Kim; Seunghee Cha; Kyudong Han (Genes & Genomics, 2025)

Soil carbon stability regulate carbon dynamics following large-scale afforestation - Qi Zhang; Hanyu Liu; Jiale He; Xinyu Cha; Shuohong Zhang; Yuqing Zhao; Yingyi Liu; Guangxin Ren; Xiaojiao Wang; Gaihe Yang; Yongzhong Feng; Chengjie Ren; et al. (Journal of Environmental Management, 2025)

Characteristics of elevated PM2.5 events driven by enhanced organic compound concentrations in a South Korean residential city - Hye-Ji Lee; Hyo-Won Lee; Sung-Won Park; Ji-Won Jeon; Pyung-Rae Kim; Kyung-Hwan Kwak; Young-Ji Han; Thomas M. Holsen; Seung-Ha Lee; Hyun-Gu Jung; Seung-Hwan Cha; Jung-Min Park; et al. (Atmospheric Environment, 2025)

A Global Meta‐Analysis of Land Use Change on Soil Mineral‐Associated and Particulate Organic Carbon - Yuqing Zhao; Yulin Xu; Xinyu Cha; Peng Zhang; Yifan Li; Andong Cai; Zhenghu Zhou; Gaihe Yang; Xinhui Han; Chengjie Ren (Global Change Biology, 2025)
Separating soil organic carbon (SOC) into mineral‐associated organic carbon (MAOC) and particulate organic carbon (POC) enables accurate prediction of SOC vulnerability to land use change (LUC). Here, we synthesize the responses of soil MAOC and POC to LUC, including land restoration and degradation, from 693 soil observations globally. We observed a large increase in soil MAOC and POC after restoration and a greater decline after degradation, but the magnitude and proportion of these two carbon fractions (fMAOC and fPOC) varied with LUC. POC, in comparison with MAOC, responded more sensitively to LUC, suggesting that POC was more vulnerable to environmental change. Using observed duration relationships, we found that the fraction of POC (fPOC) was higher at the early stage of restoration but lower at the late stage, projecting that soil carbon stability declined after short‐term restoration but gradually increased after long‐term restoration. Further analysis showed the context‐dependent effects of LUC on carbon fractions: in arid or carbon‐poor topsoil, restoration greatly increased soil carbon fractions and fPOC, while in humid or carbon‐rich topsoil, degradation resulted in large decreases in POC and MAOC, especially POC. Overall, we highlight the importance of soil fractions, particularly POC, in predicting soil carbon stability and suggest that incorporating climate and initial carbon status in models of soil carbon dynamics helps to accurately predict future carbon sink potential.

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Loliolide combats glutamate-induced neurotoxicity by oxidative stress through MAPK/Nrf2 pathway in hippocampal neuronal cells - Hyun-Soo Kim; Jayeon Cheon; Kirinde Gedara Isuru Sandanuwan Kirindage; Arachchige Maheshika Kumari Jayasinghe; Eui-Jeong Han; Sang-Myun Park; Ginnae Ahn; Seon-Heui Cha (Algal Research, 2025)

Mechanistic insight into airborne particulate matter PM10 as an environmental hazard for hemorrhagic stroke: Evidence from in vitro and in vivo studies - Chae Hwan Lee; Moon Han Chang; Young Ho Koh; Seung Pil Pack; Minseok Seo; Hanvit Cha; Jin Hyup Lee (Journal of Hazardous Materials, 2024)

Synthesis of biosurfactants from polyethylene waste via an integrated chemical and biological process - Achmad Buhori; Juwon Lee; Min Ji Cha; Jung Ho Ahn; Sung Ok Han; Jae-Wook Choi; Kwang Ho Kim; Jeong-Myeong Ha; Gyeongtaek Gong; Chun-Jae Yoo (Journal of Environmental Chemical Engineering, 2024)

Variation of volatile compounds and sensory profile for Protaetia brevitarsis larvae fermented with lactic acid bacteria and yeast - Ji Yoon Cha; Jaejoon Han; JeongAe Heo; Hwan Hee Yu; Yea-Ji Kim; Hae Won Jang; Mi-Ran Kim; Yun-Sang Choi (Food Chemistry, 2024)

Electrocatalytic carbon dioxide conversion to formate using gas-diffusion electrodes with group 12–15 metals - Guangxia Piao; Gukgyeong Yu; Seonghun Kim; Jin Sun Cha; Dong Suk Han; Hyunwoong Park (Journal of Environmental Chemical Engineering, 2024)

Modeling of cryogenic cracking behavior of tight sandstone under confinement - Lei Wang; Xinchuang Yan; Bo Gou; Songcai Han; Minsu Cha; Jingchun Zhang (Geomechanics for Energy and the Environment, 2024)

Regulation of nutrient addition-induced priming effect by both soil C accessibility and nutrient limitation in afforested ecosystem - Shuohong Zhang; Yulin Xu; Mengtao Zheng; Wanlin Yang; Yuxiao Wang; Shuang Liu; Yuqing Zhao; Xinyu Cha; Fazhu Zhao; Xinhui Han; Gaihe Yang; Chao Zhang; et al. (CATENA, 2024)

Nitrogen addition-driven soil organic carbon stability depends on the fractions of particulate and mineral-associated organic carbon - Yulin Xu; Yuqing Zhao; Xinyu Cha; Wanlin Yang; Mengtao Zheng; Shuang Liu; Yuxiao Wang; Andong Cai; Xinhui Han; Gaihe Yang; Chengjie Ren (Nutrient Cycling in Agroecosystems, 2024)

Lattice-matched in-situ-formed 1D perovskite phase in Multi-dimensional solar cells achieving high phase stability and favorable energy landscape - Jeongbeom Cha; Cheong Beom Lee; Su Min Park; Dohun Baek; Sunkyu Kim; Se Gyo Han; Haedam Jin; Seok Joo Yang; Jongchul Lim; Kyeounghak Kim; Min Kim (Chemical Engineering Journal, 2024)

Effects of extracellular vesicles derived from steroids-primed oviductal epithelial cells on porcine in vitro embryonic development - Seonggyu Bang; Ahmad Yar Qamar; Xun Fang; Heyyoung Kim; Ayeong Han; Heejae Kang; Dabin Cha; Joohyun Shim; Jun-Hyeong Kim; Kimyung Choi; Sung Ho Yun; Hayoung Lee; et al. (Theriogenology, 2023)

Evaluation of the 52-week chronic toxicity of a novel phthalate-free plasticizer, Eco-DEHCH (bis(2-ethylhexyl) cyclohexane-1,4-dicarboxylate), in Han Wistar rats - Ji-Young Lee; Hyo-Jeong Han; Soo Min Ko; Da Som Jeong; Jiyeon Kang; Dong Hyun Lee; Hwa Jun Cha; Woo-Chan Son (Food and Chemical Toxicology, 2023)

Multipurpose advanced split T7 promoter-based transcription amplification for ultrasensitive molecular diagnostics - Jiye Shin; Taehwi Yoon; Daehan Nam; Doyeon Kim; Seokjoon Kim; Byung Seok Cha; Eun Sung Lee; Youngjun Jang; Seokhwan Kim; Jinjoo Han; Hyun-Jung Choi; Ki Soo Park (Chemical Engineering Journal, 2023)

Adipose stem cell transplantation using adhesive protein-based viscous immiscible liquid for cartilage reconstruction - Seong-Woo Maeng; Ji-Yun Ko; Tae Yoon Park; Jinyoung Yun; So Hyun Park; Sang Jun Han; Kye Il Joo; Seongmin Ha; Mingoo Jee; Gun-Il Im; Hyung Joon Cha (Chemical Engineering Journal, 2023)

Influence of mobile phase composition on the analytical sensitivity of LC–ESI–MS/MS for the concurrent analysis of bisphenols, parabens, chlorophenols, benzophenones, and alkylphenols - Kang Mi Lee; Sang Moon Han; Hyeon-Jeong Lee; Minsik Kang; Tae Young Jeong; Junghyun Son; Hophil Min; Sangwon Cha; Han Bin Oh; Won Keun Oh; Jaeick Lee (Environmental Research, 2023)

Acetylshikonin induces apoptosis of human osteosarcoma U2OS cells by triggering ROS-dependent multiple signal pathways - Hyo Sun Cha; Han Ki Lee; See-Hyoung Park; Myeong Jin Nam (Toxicology in Vitro, 2023)

Properties of river organic carbon affected by wastewater treatment plants - Eun-Ju Lee; Seung-Cheol Lee; Kyuyeon Lee; Ji-Yeon Cha; Yea-Na Han; Seok Gyu Kim; Neung-Hwan Oh (Science of The Total Environment, 2023)

Synthesis of gelatin aerogel-containing Al-metal organic framework for the removal of phenolic contaminants from aqueous solutions - Taeyeon Kim; Keunyoung Yun; Nahyun Kim; Byungjun Cha; Jonghun Han; Lewis Kamande Njaramba; S.SD. Elanchezhiyan; Chang Min Park (Journal of Water Process Engineering, 2023)

The inflammatory signature in monocytes of Sjögren’s syndrome and systemic lupus erythematosus, revealed by the integrated Reactome and drug target analysis - Kyung Eun Lee; Seyoung Mun; Song-mi Kim; Wonseok Shin; Won Jung; Joon Paek; Jungnam Lee; Erin Hudson; Wesley H. Reeves; Kyudong Han; Seunghee Cha (Genes & Genomics, 2022)

Whole Genome Sequencing and Biological Characteristics of Two Strains of Porcine Escherichia coli Isolated from Saba Pigs - Bo Zhang; Weiwei Zhao; Bin Gao; Chunlan Shan; Xi Wang; Quan Wan; Jing Deng; Jinglong Cha; Bingxun Chen; Dongmei Han; Libo Gao; Pingxing Ao; et al. (Current Microbiology, 2022)

Utility of plasma cell-free DNA detection using homobifunctional imidoesters using a microfluidic system for diagnosing active tuberculosis - Joung Ha Park; Bonhan Koo; Min Jae Kim; Hyo Joo Lee; Hye-Hee Cha; Ji Yeun Kim; Sei Won Lee; Yong Shin; Sung-Han Kim (Infectious Diseases, 2022)

Frequency of putative enteric zoster diagnosed using saliva samples in patients with abdominal pain: a prospective study - Sang Hyun Ra; Ji-Soo Kwon; Ji Yeun Kim; Hye-Hee Cha; Hyun-Jung Lee; Jiwon Jung; Min Jae Kim; Yong Pil Chong; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; Won Young Kim; et al. (Infectious Diseases, 2021)

Osteogenic Response of MC3T3-E1 and Raw264.7 in the 3D-Encapsulated Co-Culture Environment - Jungju Kim; Hao-Zhen Lyu; Chisung Jung; Kyung Mee Lee; Shi Huan Han; Jae Hyup Lee; Misun Cha (Tissue Engineering and Regenerative Medicine, 2021)

Spirosoma aureum sp. nov., and Hymenobacter russus sp. nov., radiation-resistant bacteria in Cytophagales order isolated from soil - Soohyun Maeng; Yuna Park; Joo Hyun Han; Sang Eun Lee; Jing Zhang; Min-Kyu Kim; In-Tae Cha; Ki-eun Lee; Byoung-Hee Lee; Myung Kyum Kim (Antonie van Leeuwenhoek, 2020)

Rhodocytophaga rosea sp. nov. and Nibribacter ruber sp. nov., two radiation-resistant bacteria isolated from soil - Yuna Park; Soohyun Maeng; Joo Hyun Han; Sang Eun Lee; Jing Zhang; Min-Kyu Kim; In-Tae Cha; Ki-eun Lee; Byoung-Hee Lee; Myung Kyum Kim (Antonie van Leeuwenhoek, 2020)

Analysis of KAP1 expression patterns and human endogenous retrovirus Env proteins in ovarian cancer - Kyung-Yoon Jeon; Eun-Ji Ko; Young Lim Oh; Hongbae Kim; Wan Kyu Eo; Ari Kim; Han Gyu Sun; Mee Sun Ock; Ki Hyung Kim; Hee-Jae Cha (Genes & Genomics, 2020)

Pontibacter pudoricolor sp. nov., and Pontibacter russatus sp. nov. radiation-resistant bacteria isolated from soil - Soohyun Maeng; Yuna Park; Sang Eun Lee; Joo Hyun Han; In-Tae Cha; Ki-eun Lee; Byoung-Hee Lee; Myung Kyum Kim (Antonie van Leeuwenhoek, 2020)

Evaluating the impact of suramin additive on CHO cells producing Fc-fusion protein - Jin-Hyuk Lim; Hyun-Myoung Cha; Hye-Jin Han; Dong-Il Kim (Biotechnology Letters, 2019)

Association of COX2 −765G>C promoter polymorphism and coronary artery disease in Korean population - In Jai Kim; Sang Hoon Kim; Dong Hoon Cha; Sang Wook Lim; Jae Youn Moon; Jung Oh Kim; Chang Soo Ryu; Han Sung Park; Jung Hoon Sung; Nam Keun Kim (Genes & Genomics, 2019)

Genetic diversity and population structure of Kichulchoia multifasciata in South Korea - Han-Gyu Bae; Casey Nightingale; Duck Hee Jeoung; Sunho Cha; Hyung-Bae Jeon; Hangkyo Lim; Ho Young Suk (Conservation Genetics, 2019)

Methoxetamine Induces Cytotoxicity in H9c2 Cells: Possible Role of p21 Protein (Cdc42/Rac)-Activated Kinase 1 - Kyung Sik Yoon; Sun Mi Gu; Santosh Lamichhane; Kyoung Moon Han; Jisoon Shin; Young-Hoon Kim; Soo Kyung Suh; Hye Jin Cha; Jaesuk Yun (Cardiovascular Toxicology, 2019)

Pseudofrancisella aestuarii gen. nov., sp. nov., a novel member of the family Francisellaceae isolated from estuarine seawater - Min-Ling Zheng; Jian-Yu Jiao; Lei Dong; Ming-Xian Han; Liang-Hui Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Aerobic vaginitis in late pregnancy and outcomes of pregnancy - Cha Han; Huiyang Li; Lulu Han; Chen Wang; Ye Yan; Wenhui Qi; Aiping Fan; Yingmei Wang; Fengxia Xue (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Multiplex PCR using YeaD and 16S rRNA gene to identify major pathogens in vibriosis of Litopenaeus vannamei - Yeong-Jong Han; Ara Jo; So-Won Kim; Hee-Eun Lee; Young Chul Kim; Hyun Do Jeong; Yung Hyun Choi; Suhkmann Kim; Hee-Jae Cha; Heui-Soo Kim (Genes & Genomics, 2019)

Electrophysiological Signatures of Intrinsic Functional Connectivity Related to rTMS Treatment for Mal de Debarquement Syndrome - Yoon-Hee Cha; Guofa Shou; Diamond Gleghorn; Benjamin C. Doudican; Han Yuan; Lei Ding (Brain Topography, 2018)

Effects of 7-MEGA TM 500 on Oxidative Stress, Inflammation, and Skin Regeneration in H 2 O 2 -Treated Skin Cells - In-Bong Song; Hyejung Gu; Hye-Ju Han; Na-Young Lee; Ji-Yun Cha; Yeon-Kyong Son; Jungkee Kwon (Toxicological Research, 2018)

Plant synthetic GP4 and GP5 proteins from porcine reproductive and respiratory syndrome virus elicit immune responses in pigs - Chul Han An; Salik Nazki; Sung-Chul Park; Yu Jeong Jeong; Ju Huck Lee; Su-Jin Park; Amina Khatun; Won-Il Kim; Youn-Il Park; Jae Cheol Jeong; Cha Young Kim (Planta, 2018)

A synthetic cannabinoid JWH-210 reduces lymphoid organ weights and T-cell activator levels in mice via CB2 receptors - Sun Mi Gu; Hyun Jin Lee; Tac-hyung Lee; Yun Jeong Song; Young-Hoon Kim; Kyoung-Moon Han; Jisoon Shin; Hye-Kyung Park; Hyung Soo Kim; Hye Jin Cha; Jaesuk Yun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Fucoidan inhibits lipopolysaccharide-induced inflammatory responses in RAW 264.7 macrophages and zebrafish larvae - Jin-Woo Jeong; Su Jung Hwang; Min Ho Han; Dae-Sung Lee; Jong Su Yoo; Il-Whan Choi; Hee-Jae Cha; Suhkmann Kim; Heui-Soo Kim; Gi-Young Kim; You-Jin Jeon; Hyo-Jong Lee; et al. (Molecular & Cellular Toxicology, 2017)

Association of folate metabolism gene polymorphisms and haplotype combination with pulmonary embolism risk in Chinese Han population - Xin Li; Ling Weng; Baihe Han; Yingnan Dai; Li Cha; Shujun Yan; Enze Jin (Mammalian Genome, 2017)

Enhanced production of resveratrol derivatives in tobacco plants by improving the metabolic flux of intermediates in the phenylpropanoid pathway - Yu Jeong Jeong; Chul Han An; Su Gyeong Woo; Ji Hye Park; Ki-Won Lee; Sang-Hoon Lee; Yeonggil Rim; Hyung Jae Jeong; Young Bae Ryu; Cha Young Kim (Plant Molecular Biology, 2016)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

MicroRNA expression profiling of p-phenylenediamine treatment in human keratinocyte cell line - Hwa Jun Cha; Ok-Kyu Lee; Soo Yeon Kim; Jung-Min Ko; Su Young Kim; Ji Hye Son; Hyun Joo Han; Shunhua Li; Soo Young Kim; Kyu Joong Ahn; In-Sook An; Sungkwan An; et al. (Molecular & Cellular Toxicology, 2015)

Induction of immune responses in mice and pigs by oral administration of classical swine fever virus E2 protein expressed in rice calli - Myunghwan Jung; Yun Ji Shin; Ju Kim; Seung-Bin Cha; Won-Jung Lee; Min-Kyoung Shin; Seung Won Shin; Moon-Sik Yang; Yong-Suk Jang; Tae-Ho Kwon; Han Sang Yoo (Archives of Virology, 2014)

House dust mite allergen Der f 2 induces interleukin-13 expression by activating the PI3K/Akt pathway - Eun Ji Ro; Pu-Hyeon Cha; Hyun-Yi Kim; Yong-Hee Cho; Jung-Won Park; Joong-Soo Han; Kang-Yell Choi (Immunologic Research, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

Occurrence of black rot of cultivated mushrooms (Flammulina velutipes) caused by Pseudomonas tolaasii in Korea - Hye-Su Han; Chang-Sung Jhune; Jong-Chun Cheong; Jin-A Oh; Won-Sik Kong; Jae-Soon Cha; Chan-Jung Lee (European Journal of Plant Pathology, 2012)

Capsaicin-induced apoptosis in the human glioblastoma U87MG cells via p-38 MAPK and Bcl-2/Bax signaling pathway - Jin Ho Jeon; Yoon Ji Choi; In Ho Han; Byung Kwan Choi; Seung Heon Cha; Won Ho Cho (Molecular & Cellular Toxicology, 2012)

Potential role of the rice OsCCS52A gene in endoreduplication - Mukhamad Su’udi; Joon-Yung Cha; Min Hee Jung; Netty Ermawati; Chang-deok Han; Min Gab Kim; Young-Min Woo; Daeyoung Son (Planta, 2012)

Human chorionic-plate-derived mesenchymal stem cells and Wharton’s jelly-derived mesenchymal stem cells: a comparative analysis of their potential as placenta-derived stem cells - Mi Jeong Kim; Kyung Seon Shin; Jin Hee Jeon; Dong Ryul Lee; Sung Han Shim; Jin Kyeoung Kim; Dong-Hyun Cha; Tae Ki Yoon; Gi Jin Kim (Cell and Tissue Research, 2011)

Childhood cancer mortality and socioeconomic position in South Korea: a national population-based birth cohort study - Kyoung Ae Kong; Young-Ho Khang; Eun Shil Cha; Eun Kyeong Moon; Yo Han Lee; Won Jin Lee (Cancer Causes & Control, 2010)

Analysis of the helicase gene of Korean swine hepatitis E virus isolates and trends in viral infection - Won-Jung Lee; Mi Lan Kang; Seung-Bin Cha; Bong-Kyun Park; In-Soo Choi; Han Sang Yoo (Archives of Virology, 2009)

SLC11A1 Polymorphisms Are Associated with the Risk of Chronic Obstructive Pulmonary Disease in a Korean Population - Eun Jin Kim; Kyung Mee Kim; Sun Ha Park; Jong Sik Kim; Won Kee Lee; Sung Ick Cha; Chang Ho Kim; Young Mo Kang; Sung Beom Han; Tae Hoon Jung; Jae Yong Park (Biochemical Genetics, 2008)

A Ds-insertion mutant of OSH6 (Oryza sativa Homeobox 6) exhibits outgrowth of vestigial leaf-like structures, bracts, in rice - Sung Han Park; Chul Min Kim; Byoung Il Je; Su Hyun Park; Soon Ju Park; Hai Long Piao; Yuan-hu Xuan; Mi Sook Choe; Kouji Satoh; Shoshi Kikuchi; Kon Ho Lee; Young Soon Cha; et al. (Planta, 2007)

Analysis of gene-trap Ds rice populations in Korea - Sung Han Park; Nam Soo Jun; Chul Min Kim; Tae Yong Oh; Jin Huang; Yuan-hu Xuan; Soon Ju Park; Byoung Il Je; Hai Long Piao; Soo Hyun Park; Young Soon Cha; Byung Ohg Ahn; et al. (Plant Molecular Biology, 2007)

Polymorphism and Genomic Structure of the A+T-Rich Region of Mitochondrial DNA in the Oriental Mole Cricket, Gryllotalpa Orientalis (Orthoptera: Gryllotalpidae) - Iksoo Kim; So Young Cha; Mi Ae Kim; Young Shin Lee; Kwang Sik Lee; Yong Soo Choi; Jae Sam Hwang; Byung Rae Jin; Yeon Soo Han (Biochemical Genetics, 2007)

Efficient transient expression and transformation of PEG-mediated gene uptake into mesophyll protoplasts of pepper (Capsicum annuum L.) - Joo Mi Jeon; Nam Young Ahn; Bo Hwa Son; Cha Young Kim; Chang-deok Han; Gun-Do Kim; Sang Wan Gal; Sung-Ho Lee (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

High glucose and angiotensin II increase β1 integrin and integrin-linked kinase synthesis in cultured mouse podocytes - Sang Youb Han; Young Sun Kang; Yi Hwa Jee; Kum Hyun Han; Dae Ryong Cha; Shin Wook Kang; Dae Suk Han (Cell and Tissue Research, 2006)

Renal tissue reconstitution by the implantation of renal segments on biodegradable polymer scaffolds - Sang-Soo Kim; Heung Jae Park; Joungho Han; Cha Yong Choi; Byung-Soo Kim (Biotechnology Letters, 2003)

Stereochemical control in diastereoselective reduction of α-substituted-β-ketoesters using a reductase purified from Kluyveromyces marxianus - Joo Hwan Cha; Ae Nim Pae; Kyung Il Choi; Yong Seo Cho; Wook Hyun Kim; Ye Sun Han; Hong-Chul Yun; Jongsoo Lee; Hun Yeong Koh; Eun Lee (Biotechnology Letters, 2002)

Changes of Flow Characteristics by Stenting in Aneurysm Models: Influence of Aneurysm Geometry and Stent Porosity - Kyehan Rhee; Moon Hee Han; Sang Hoon Cha (Annals of Biomedical Engineering, 2002)

A new class II rice chitinase, Rcht2, whose induction by fungal elicitor is abolished by protein phosphatase 1 and 2A inhibitor - Cha Young Kim; Sang Wan Gal; Mi Sook Choe; Sun Yong Jeong; Soo In Lee; Yong Hwa Cheong; Sang Hyoung Lee; Young Ju Choi; Chang-deok Han; Kyu Young Kang; Moo Je Cho (Plant Molecular Biology, 1998)